Gender analysis for social equity in aquatic food systems: a research agenda for strengthening fisheries science to support transformational change - Hapke, Holly M. (Frontiers in Sustainable Food Systems, 2025)
Women’s involvement in the fisheries and aquaculture sector remains invisible and undervalued, and women have been relatively excluded from national development policies and programs. The neglect of post-harvesting activities and the exclusion of women from research and policy have created gender inequities and differential impacts on men and women – often to women’s detriment. Failure to account for sex, gender and other social factors in fisheries and aquaculture research furthermore results in weak science and, often, policy failure. While much progress has been made in documenting women’s roles in aquatic food systems, broadening and deepening the scope of theoretically informed gender analysis in fisheries and aquaculture research is not only necessary for achieving social equity in the sector, it is critical for the development of robust fisheries and aquaculture science. This essay delineates several concepts and presents a framework for gender analysis that will strengthen fisheries and aquaculture science and may support transformational change toward gender equity in aquatic food systems.